Bicultural managers leading multicultural teams: a conceptual case study. (26th June 2020) - Batsa, Eric Tetteh; Abadir, Sameh; Neubert, Michael
Biculturals are recognised as an important segment of managers. However, organisational leaders have a gap in knowledge about this group's distinctive experiences. A conceptual case study design was followed through a literature review approach to present the present state of knowledge focused on current research findings on bicultural managers' boundary spanning competencies and multicultural team effectiveness. This study is framed by three key concepts of bicultural competence, boundary spanning, and leadership emergence in multicultural teams. This integrative literature review provides in-depth knowledge for understanding the management experiences of biculturals and the implications of their competencies and skills in leading multicultural teams. Bicultural managers possess an understanding of multiple cultures that can enhance team outcomes and complex team-level competencies associated with better performance. This integrative literature review can be utilised by future researchers as foundational material in studies to extend theoretical foundations and to extend the results of prior related studies.